Imagens que falam: uma investigação fotoetnográfica da performance cultural goianiense (2014-2016) - Silva, André Carlos Conrado Inácio da (2016)
The word performance was popularized and became appellant in everyday human being. However, they make use of it without understanding the size and strength she has. . The performance takes place in all areas of our life, she runs the kitchen at the time of cooking, in sports, at work, on the floor, finally the performance is a term loaded with meanings and synthesis shows that our life is structured with ways behavior and gestural expression that a social attitude that is evident in daily living. The dissertational work images that speak: A pictorial ethnographic research goianiense cultural performance (2014-2016), sought to demonstrate how to constitute the daily lives of the city of Goiania cultural performance of passers-by that it circulating in their day-to-day. For this, we used the Photoethnography in a collection of images made through photographs taken at various points of the city, which were later transformed into lick lick and taken for public reception in the same places where photographed form. With the reception process we seek to identify the goianiense or goianiense recognize the images its own cultural performance or not. So in the receptive process we conducted interviews with the receiver public that were later used for data analysis on procedural research. This time, the results led to a gestural performance goianiense and goianiense that became evident in his statements on the existence of an identity - performative than is to be a goianiense or goianiense. This work is an invitation to get to know how to built and present in living daily "be goianiense".